Guest Editorial: Impact of Integrated Intelligent Information and Analytical Systems on Society - Asadullah Shaikh (Journal of Information Technology Management)
The Special Issue of the Journal of Information Technology Management (JITM) is publishing very selective papers on information management, technology in higher education, integrated systems, enterprise management, cultural thoughts, strategic contributions, management information systems, and cloud computing. We received numerous papers for this special issue but after an extensive peer-review process, 10 papers were finally selected for publication. The current special issue consisted of areas viz Integrated Intelligent Systems, Analytical Systems, and Enterprise Management.